2006
DOI: 10.1177/1545968306289289
|View full text |Cite
|
Sign up to set email alerts
|

Primary Motor Area Activation during Precision-Demanding versus Simple Finger Movement

Abstract: The authors used functional magnetic resonance imaging to explore whether the primary motor area (M1) serves a processing role in a finger-movement tracking task, emphasizing attention to accuracy, beyond its execution role of simple movements, with no attention to accuracy. Twenty healthy subjects performed alternating conditions: Rest, involving no finger movement; Track, involving careful control of a cursor along a target pathway with finger extension/flexion movements; and Move, involving finger extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…Recent TMS studies have shown changes in corticospinal synaptic activity and/or improved synaptic efficacy of specific intracortical pathways within the M1 following a period of motor skill training [31]. It is noteworthy that the more demanding tasks result in greater activation and higher facilitation than less demanding tasks [31,33]. …”
Section: Neuro-physiological Processes Associated With Brain Activmentioning
confidence: 99%
“…Recent TMS studies have shown changes in corticospinal synaptic activity and/or improved synaptic efficacy of specific intracortical pathways within the M1 following a period of motor skill training [31]. It is noteworthy that the more demanding tasks result in greater activation and higher facilitation than less demanding tasks [31,33]. …”
Section: Neuro-physiological Processes Associated With Brain Activmentioning
confidence: 99%
“…A recent functional imaging study by Carey et al (2006) confirmed the influence of task demand in terms of precision on the motor cortex. They compared activation levels when participants used their index finger either in a precision tracking task or to perform simple flexion/ extension movements.…”
Section: Origin and Site Of Mep Facilitationmentioning
confidence: 90%
“…For instance, Flament et al (1993) compared MEP facilitation in the first dorsal interosseus (FDI) under various grasp actions requiring complex synergistic patterns of muscle activity with that elicited during isolated index finger movement and observed greater facilitation for the complex tasks. More recent TMS and neuroimaging studies in humans have confirmed that task demand in terms of complexity and precision is indeed a critical factor in modulating corticospinal excitability when executing hand actions (Tinazzi and Zanette 1998;Carey et al 2006;Ni et al 2006;Bonnard et al 2007). …”
Section: Introductionmentioning
confidence: 97%
“…(Castro-Alamancos and Borrel, 1995;Friel et al, 2000;Frost et al, 2003;Remple et al, 2001;Kleim et al, 2003;Gharbawie et al, 2005;Nudo and Milliken, 1996;Traversa et al, 1997;Cicinelli et al, 1997) These studies show that ablation of the remapped cortex reinstates behavioural impairments (Castro-Alamancos and Borrel, 1995) and physical therapy induces an increase in motor map size that correlates with significant functional improvement (Liepert et al, 1998;Liepert et al, 2000). Functional imaging has been used to demonstrate that patients with stroke-induced sensorimotor impairments show a reorganization of cortical activity evoked by stimulation of the stroke-affected limbs after stroke (Calautti and Baron, 2003;Carey et al, 2006;Chollet et al, 1991;Cramer et al, 1997;Cramer and Chopp, 2000;Herholz and Heiss, 2000;Jaillard et al, 2005;Nelles et al, 1999a;Nelles et al, 1999b;Seitz et al, 1998;Ward et al, 2003b;Ward et al, 2003ab;Ward et al, 2006;Weiller et al, 1993). Strikingly, increased activity in novel ipsilesional sensorimotor areas has been correlated with improved recovery in human www.intechopen.com stroke patients (Fridman et al, 2004;Johansen-Berg et al, 2002b;Johansen-Berg et al, 2002a;Schaechter et al, 2006).…”
Section: Plasticity In Peri-infarct Cortexmentioning
confidence: 99%